The Blood Ship - Springer, Norman, 1888-1974 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Blood Ship" by Norman Springer is a novel written in the early 20th century. The story unfolds as it introduces Captain Shreve, who is approached by a chatty writer seeking material about "King" Waldon, a legendary figure from the South Seas. The plot revolves around the ship, the "Golden Bough", and its dangerous crew, setting the stage for a gripping tale of adventure and moral conflict. At the start of the book, we witness the witty banter between Captain Shreve and the loquacious writer aboard the "Golden Bough" as they prepare for a sea voyage. The writer is particularly eager to gather stories about Waldon and his mysterious past, intriguing Shreve and his mate, Briggs. Meanwhile, Shreve harbors memories of the "Golden Bough"'s glorious history, realizing it has played a significant role in his own life, intertwined with themes of danger, love, and sacrifice. As the narrative progresses, the characters' fates become interlinked, especially with the enigmatic presence of a man named Newman, who appears to have his own dark reasons for joining the ill-fated ship. This complexity hints at deeper layers of the narrative, promising a dynamic exploration of the human condition amid perilous maritime adventures. (This is an automatically generated summary.)
Release date is 2005-12-30
E-text prepared by Al Haines
Keywords: Sea stories; Mutiny -- Fiction